Etic and emic approaches to the collective memory in media coverage of the Hasidic pilgrimage to Uman. (December 2018) - Marchenko, Alla
Abstract: This article compares two approaches to media coverage of the annual Hasidic pilgrimage to Uman (contemporary Ukraine) in Ukrainian and American Jewish newspapers (2011–2015). Research suggests that either emic or etic approaches to collective memory characterize both media, whereas each of them has different foci: either "communicative memory" or "cultural memory" (Assmann). Ukrainian media shows two main discourses: "Pilgrimage as a disaster" and "Pilgrimage as an unknown phenomenon", while two other discourses – "Pilgrimage as a challenge" and "Pilgrimage as a source of inspiration" characterize American Jewish media. Mutual vilification found in the newspapers of both sides, and the strategies of "othering" similarly allocate either the Hasidic pilgrims or the locals in Ukraine.